2017
DOI: 10.1007/s00259-017-3846-6
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic 18F–FET PET for the characterization of gliomas defined by IDH and 1p/19q status

Abstract: Data suggest that static and dynamic F-FET PET parameters may allow determining non-invasively the IDH mutation status. However, IDH mutated and 1p/19q co-deleted oligodendrogliomas cannot be differentiated from glioblastomas and astrocytomas byF-FET PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 37 publications
4
58
0
1
Order By: Relevance
“…In general, MET uptakes in IDH1-wildtype gliomas were significantly higher compared with those in IDH1-mutant gliomas [6,7,8]. However, several amino acid PET studies showed paradoxically higher tracer uptakes in IDH-mutant gliomas, especially with oligodendroglial components, compared with counterpart IDH1-wildtype tumours [8,9,10]. These results suggest that amino acid PET studies are not fully consistent or accurate for differentiating glioma at diagnosis based on the 2016 WHO classification.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…In general, MET uptakes in IDH1-wildtype gliomas were significantly higher compared with those in IDH1-mutant gliomas [6,7,8]. However, several amino acid PET studies showed paradoxically higher tracer uptakes in IDH-mutant gliomas, especially with oligodendroglial components, compared with counterpart IDH1-wildtype tumours [8,9,10]. These results suggest that amino acid PET studies are not fully consistent or accurate for differentiating glioma at diagnosis based on the 2016 WHO classification.…”
Section: Introductionmentioning
confidence: 83%
“…In fact, AOs (median 5.07, IQR 4.72-7.21) showed increased MET uptake as high as those in GBMs (median 6.19, IQR 4.63-7.41), in which most of them were IDH1-wild type tumours in the present study. Several amino acid PET studies showed paradoxically higher tracer uptakes in IDH-mutant gliomas and the inability to predict the IDH1 mutation status among grade Ⅱ and Ⅲ gliomas [9,10]. These results suggest that the use of amino acid PET for differentiating glioma at diagnosis may be useful but is subject to controversy.…”
Section: Based On the 2016 Who Classification Met-pet Studies In Patmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, few studies investigated in LGGs the correlations of metabolic and structural MRI findings with molecular features and histological grade 37,38 . Among these studies, few only examined imaging findings in the context of the new WHO brain tumor classification 12,15,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, based on these preliminary data, we are currently not able to identify molecular classes using current amino acid PET techniques. A recently published study by Verger et al [46] concluded that static and dynamic 18-F-FET PET has a statistically significant role in discriminating between IDH mutated astrocytomas and IDH wild-type glioblastomas, although the method lacks value when discriminating between these two groups of gliomas and IDH mutated/1p19q codeleted oligodendrogliomas. Since most of the relevant literature is from the era before molecular markers, further research should be encouraged.…”
Section: Discussionmentioning
confidence: 99%